Innovations in foreign trade management under pre-war neo protectionism conditions - Boichenko M. V.; Boiarkin, M. O (НТУ "ДП", 2023)
Results. This study offers recommendations for overcoming the risks of foreign economic activity, in particular the relocation of jobs, changes in trade and payment balances on the example of individual countries, as well as the use of discriminatory measures against exporting firms from Ukraine. It is demonstrated that before the war, Ukrainian firms that exported their products and services to foreign markets faced fierce competition for both customers and investments. As most of the world prioritizes trade liberalization, many so-called «developed countries» suffer from the social and political consequences of the global distribution of wealth and labor, which include the movement of jobs abroad and rising unemployment. It was revealed that more and more countries are applying neo-protectionism measures to protect local markets and strengthen the competitive positions of national businesses, so the management of Ukrainian firms should take these risks into account when developing their own foreign trade strategies. Результати. У цьому дослідженні запропоновано рекомендації щодо подолання ризиків зовнішньоекономічної діяльності, зокрема переміщення робочих місць, зміну торговельного та платіжного балансів на прикладі окремих країн, а також застосування дискримінаційних заходів проти фірм-експортерів з України. Продемонстровано, що до війни українські фірми, що експортували свою продукцію та послуги на зовнішні ринки, стикалися з гострою конкуренцією як за клієнтів, так і за інвестиції. Оскільки більшість країн світу проголошує пріоритет лібералізації торгівлі, багато так званих «розвинених країн» страждають від соціальних і політичних наслідків глобального розподілу багатства та праці, які включають переміщення робочих місць за кордон і підвищення рівня безробіття. Виявлено, що все більше країн застосовують заходи неопротекціонізму для захисту місцевих ринків і зміцнення конкурентних позицій національного бізнесу, тому керівництво українських фірм має враховувати ці ризики при розробці власних стратегій зовнішньої торгівлі.
Інновації у менеджменті зовнішньоекономічної діяльності в умовах передвоєнного неопротекціонізму
Keywords: export activities; free trade; foreign trade management; international trade; neo- protectionism; trade balance; innovations; кспортна діяльність; вільна торгівля; менеджмент; зовнішньоекономічної діяльності; міжнародна торгівля; неопротекціонізм; торговельний баланс; інновації.